A new structural model for disorder in vaterite from first-principles calculations - Demichelis, Raffaella; Raiteri, Paolo; Gale, Julian; Dovesi, R. (The Royal Society of Chemistry, 2012)
Both of the previously proposed Pbnm and P6522 ordered structures for vaterite are found to be unstable transition states using first principles methods. Five stable structures are located, the lowest energy one being of P3221 symmetry. Since interconversion between these structures requires only thermal energy, this provides an additional source of disorder within the vaterite structure.